Makna simbolik ritual ruwatan satu suro di Candi Sima - Dayanti Noviyana (STABN RADEN WIJAYA WONOGIRI, 2021)
The purpose of this study was to see the history and procession of the ritual implementation of the one sura ruwatan ritual at Sima Temple and the symbolic meaning of the ruwatan one sura ritual in Sima Temple, Blingoh Village, Donorojo District, Jepara Regency. The research method used in this research is descriptive qualitative research method, sampling is used to capture as much information as possible from various sources using data analysis techniques in this study starting from collecting, sorting, processing and analyzing data using interactive model analysis. The symbolic meaning of the ruwatan ritual in Sima Temple is to refuse reinforcements to rid themselves of danger.